2018
DOI: 10.1177/0306624x18784191
|View full text |Cite
|
Sign up to set email alerts
|

Can Social Support Overcome the Individual and Structural Challenges of Being a Sex Offender? Assessing the Social Support-Recidivism Link

Abstract: Social support is important for individual's successful reentry; however, little is known about how it operates or is influenced by individual and structural factors. Understanding how social support matters for individuals convicted of a sex offense is especially important as they may have a different reentry experience due to the nature of their crime and post-conviction restrictions. This study examines the nature and effects of instrumental and expressive social support from family, friends, intimate partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
0
11
0
2
Order By: Relevance
“…Some studies showed that social support from family, friends and/or partners protects person against recidivism (Bahr, Harris, Fisher, & Harker Armstrong, 2010; Hochstetler, DeLisi, & Pratt, 2010). On the other hand, some researchers found that perceived social support from family, friends or partner did not predict recidivism (Kras, 2019;Orrick et al, 2011). In this study, it has been investigated whether the individuals who have been convicted of physical violence (wounding or murder) are predicted by the perceived social support and the level of expectation after release.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies showed that social support from family, friends and/or partners protects person against recidivism (Bahr, Harris, Fisher, & Harker Armstrong, 2010; Hochstetler, DeLisi, & Pratt, 2010). On the other hand, some researchers found that perceived social support from family, friends or partner did not predict recidivism (Kras, 2019;Orrick et al, 2011). In this study, it has been investigated whether the individuals who have been convicted of physical violence (wounding or murder) are predicted by the perceived social support and the level of expectation after release.…”
Section: Discussionmentioning
confidence: 96%
“…The importance of social support, especially for the offenders, is not surprising, as it has emerged as protective factor against recidivism in numerous studies (Kras, 2019). However, in Mitchell and Galupo’s study (2018) of 69 men sexually attracted to children, participants mentioned self-control as a more important factor to not offend than supportive friends and family.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, people with a history of sexual offenses were not invited to participate in this research because of the additional barrierssuch as social stigma and enhanced monitoringto desistance for this group. For example, Kras (2019) noted that persons convicted of sexual offenses may be required to report to probation offices more often than non-sexual offenders as a condition of their release, which may affect their attendance at a place of employment.…”
Section: Sampling Participants and Ethical Permissionsmentioning
confidence: 99%